High-skilled services and development in China - Lei Fang; Berthold Herrendorf (Federal Reserve Bank of Atlanta, 2019)
We document that the employment share of high-skill-intensive services is much lower in China than in countries with similar gross domestic product (GDP) per capita. We build a model of structural change with goods and low- and high-skill-intensive services to account for this observation. We find that large distortions limit the size of high-skill-intensive services in China. If they were removed, both high-skill-intensive services and GDP per capita would increase considerably. We document a strong presence of state-owned enterprises in high-skill-intensive services and argue that this presence leads to important distortions.
Keywords: O41; O47; O51; 330; China; high-skill intensive services; structural change